An Effective Automatic Breast Cancer Identification using Vedic Mathematics. (2021) - Sumathi, R.; Indumathi, R.
Abstract: Breast cancer in recent years has been pervasive and become one of the leading causes of death. Breast cancer typically is a malignant tumour that has been start to growth from cells of the breast and eventually affects the surrounding cells. The women affected by the breast cancer cause high mortality rate. So the detection of breast cancer at an early stage helps to increase the survival rate and possibility of suitable treatment by healthcare professional. The breast cancer is detected by mammogram and followed by Biopsy. We proposed a method here to identify the breast cancer using image processing techniques which is blended with Vedic Mathematics. It consists of stages: Image pre-processing, Segmentation, Feature Extraction. In the proposed method, desired features of the cancer regions are extracted through regional descriptors. The main aim of this paper is to assist the pathologists to improve the accuracy, efficiency in detecting grade of cancer and to minimize the inter-observer variation.